Temporal and spatial characteristics of agricultural non-point source pollution in Hebei Province from 2000 to 2021 - Li, Tongtong; Niu, Yongchao; Pang, Jun; Geng, Shuang; Wang, Yangyang; Li, Ji; Xiong, Yanna; Wang, Lei (Frontiers in Environmental Science, 2024)
Agricultural non-point source pollution (ANP) had become an important source of water pollution, which seriously restricted the coordinated development of Beijing, Tianjin and Hebei. As the primary agricultural production base in the region of Beijing-Tianjin-Hebei, Hebei had serious ANP. In order to clarify the current status of ANP in Hebei and figure out the main pollution source and areas, ANP load of Hebei from 2000 to 2021 were evaluated by the export coefficient modeling (ECM) and spatial-temporal characteristics were carried out using geographic information system (GIS). In addition, ANP severity and emission characteristics of Hebei in 2021 were evaluated. The results showed that the environmental impact of ANP in southwest area was obviously more serious than that in northeast area of Hebei. Especially, ANP emissions in Hebei showed significant decreasing inflection points in 2007 and 2017, respectively, reaching a minimum by 2021. The TN and TP emissions of ANP in Hebei were 315,026.1 t and 50,323.76 t in 2021, respectively. The contribution of agricultural land, livestock and poultry breeding and rural life to TN and TP emissions were 37%, 34%, 29% and 20%, 61% and 18%, respectively. The ANP pollution mainly came from livestock and poultry breeding in Hebei Province. Based on cluster analysis, cities in Hebei were divided into 4 types, and the control strategies for ANP environment management were put forward.